Students’ Perceptions on the Use of Group Discussion Method towards English Speaking Proficiency - Suryo Sudiro; Putri Lisa Anggraini; Metyana Setyorini; Aditama Bagus Antasari; Juhansar Juhansar (Universitas Muhammadiyah Kalimantan Timur, 2022)
The researchers place a great deal of emphasis on the Group Discussion Method since it is necessary for students towards their communication proficiency. Communication is an important element to achieve better understanding among communicators. Therefore, this present study aims to discover students’ perception of using the Group Discussion Method towards their proficiency in English speaking. This research relays on a quantitative descriptive research design using a questionnaire to collect data. The questionnaire was distributed online to thirty-four respondents. The respondents are fifth-semester students of the English Language Education Department of Universitas Teknologi Yogyakarta who has learned English speaking using the Group Discussion Method. Data were analyzed using quantitative descriptive perceptions presentation. The research findings indicate that 80% of respondents state that Group Discussions Method is an interactive, friendly, innovative, and interaction-built approach between teacher and students. Besides, it also increases their English speaking proficiency since they are learning in a group where they are required to talk and discuss in English. This research is limited to small-scale respondents; thus, further researchers are recommended to conduct research with wide-scale respondents.